Molecular Docking and Interaction Analysis of Propolis Compounds Against SARS-CoV-2 Receptor: Propolis Compound Against SARS-CoV-2 Receptor - Mokhamad Fahmi Rizki Syaban; Icha Farihah Deniyati Faratisha; Khadijah Cahya Yunita; Nabila Erina Erwan; Dedy Budi Kurniawan; Gumilar Fardhani Ami Putra (Journal of Tropical Life Science, 2022)
Background: For many people, especially in developing countries, herbal medicine is the most traditional drug choice to treat all diseases including severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2 infection). Propolis is one of the popular herbal medicine which has various health benefits, particularly antiviral activity. In this molecular docking study, this investigation examined twenty-five kinds of propolis to bind SARS-CoV-2 protein with the main targets of ACE-2 and M-Pro receptors. Method: Propolis ligands were downloaded from PubChem, meanwhile ACE-2 and M-Pro receptors were downloaded from Protein Data Bank. Both ligands and targets were optimized by Pymol. The pharmacokinetic analysis was conducted using SwissADME. Molecular docking was done using PyRx 0.9 and its binding interaction was visualized by Discovery Studio. To predict the potential inhibition, this study compared the ligand-protein complex of propolis to ligands from the previous study. Result: Through the Lipinski rule, only five of twenty-five types of propolis were not qualified for the criterion. The ability to bind protein targets were various between ligands, the highest affinity to ACE-2 receptors were abietic acid, galangin, chrysin, kaempferol and acacetin, respectively. The binding affinity between ligand and M-Pro were seen weaker than ACE-2 receptor, while the strongest were kaempferol, abietic acid, acacetin, galangin and chrysin, respectively. Conclusion: Ã‚Â Kaempferol is the most potent form of propolis to bind to ACE-2 and M-Pro receptors by assessing the binding affinity and the amount of amino acid residue formation when compared to control ligands. Keywords: ACE-2 receptor, COVID-19, Main protease, Molecular docking, Propolis, SARS-CoV-2